Efficient synthesis of dipyrrolobenzenes and dipyrrolopyrazines via bidirectional gold catalysis: a combined synthetic and photophysical study - Heckershoff, Robin; Schnitzer, Tobias; Diederich, Tim; Eberle, Lukas; Krämer, Petra; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Journal of the American Chemical Society, 2022)
New N-heterocyclic fluorophores are sought-after compounds for organic electronic devices. Here, we report on a straightforward synthesis to access meta/para-dipyrrolobenzenes and para-dipyrrolopyrazines in high yields using a bidirectional gold-catalyzed cyclization strategy. The versatility of our reaction protocol was showcased by preparing dipyrroloarenes with different substituents, various functional groups, and in a multitude of substitution patterns. Furthermore, we showed that the dipyrroloarenes can be post-modified by N-alkylation to improve the solubility or bromination to yield precursors for further derivatization via cross-coupling. Investigation of the photophysical properties of the─mostly unprecedented─dipyrroloarenes identified strong blue emitters such as the diphenyl meta-dipyrrolobenzene with a quantum yield of 98%. Moreover, we showed that changes in the solvent polarity or interactions with Lewis acids such as borane can be used to fine-tune the photophysical properties of the fluorophores.
Gesehen am 24.06.2022